Manual to practical sessions on medical supervision in physical exercise, sports and clinical practice: teaching guide for students with majors in "General Medicine" and "Pediatrics" - Выходцев, А. Н. физиотерапия, лечебная физкультура 19560714 Андрей Николаевич (Siberian State Medical University, 2019)
The teaching guide presents medical supervision techniques according to the "Exercise Therapy" course. The manual describes the main methods used in performing medical examination of persons engaged in physical training. Besides, the guide demonstrates the ways to determine physical working capacity and perform medical and pedagogical supervision in clinical practice. The manual is intended for students and may be also of interest for medical doctors and specialists working in the field of recreational physical culture. The guide is compiled in accordance with Federal State Educational Standards of Higher Education for students with majors in "General Medicine" and "Pediatrics".